2020
DOI: 10.3390/antiox9030228
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Compound Isoliquiritigenin, an Antioxidant from Licorice, Suppresses Triple-Negative Breast Tumor Growth via Apoptotic Death Program Activation in Cell and Xenograft Animal Models

Abstract: Patients with triple-negative breast cancer have few therapeutic strategy options. In this study, we investigated the effect of isoliquiritigenin (ISL) on the proliferation of triple-negative breast cancer cells. We found that treatment with ISL inhibited triple-negative breast cancer cell line (MDA-MB-231) cell growth and increased cytotoxicity. ISL reduced cell cycle progression through the reduction of cyclin D1 protein expression and increased the sub-G1 phase population. The ISL-induced apoptotic cell pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 52 publications
2
36
0
2
Order By: Relevance
“…With licorice isoliquiritigenin it was reported that pretreatment of mice showed least chances rate of getting cancer attack [17]. Also consequently, there was a reduction in cell proliferation and also the induction of Ki-67 protein which also reduces the cell proliferation and the proteins like caspase-3 and p62 proteins formation were reduced [20][21][22][23][24]. This denotes that the cancerous cells were underwent autophagy.…”
Section: Resultsmentioning
confidence: 98%
“…With licorice isoliquiritigenin it was reported that pretreatment of mice showed least chances rate of getting cancer attack [17]. Also consequently, there was a reduction in cell proliferation and also the induction of Ki-67 protein which also reduces the cell proliferation and the proteins like caspase-3 and p62 proteins formation were reduced [20][21][22][23][24]. This denotes that the cancerous cells were underwent autophagy.…”
Section: Resultsmentioning
confidence: 98%
“…Lin et al (2017) demonstrated that treatment with ISL alone or in combination with doxorubicin is highly effective in sensitizing doxorubicin-resistant cancer cells, resulting in the reduced survival of cancer cells [ 142 ]. Moreover, ISL not only inhibits cancer cell growth by inducing apoptosis and autophagy, but can also enhance chemosensitivity [ 40 , 66 , 67 , 69 ]. It has also been reported that doxorubicin triggers an epithelial-to-mesenchymal transition (EMT) in TNBC through mediating the PI3K/AKT pathway.…”
Section: Isl Anti-tumor Effectsmentioning
confidence: 99%
“…It has also been reported that doxorubicin triggers an epithelial-to-mesenchymal transition (EMT) in TNBC through mediating the PI3K/AKT pathway. Interestingly, ISL also can inhibit the PI3K/AKT pathway and thus suppresses EMT and increases the antiproliferative effect [ 40 , 66 , 67 , 69 ]. ISL or its derivatives show a greater influence by regulating the miR-374a/BAX axis, the -374a/PTEN/AKT axis, or the autophagy-mediated apoptosis (p62/caspase-8) pathway, especially in TNBC [ 33 , 67 , 69 ].…”
Section: Isl Anti-tumor Effectsmentioning
confidence: 99%
See 2 more Smart Citations